GLPG1837, a CFTR potentiator, in p.Gly551Asp (G551D)-CF patients: An open-label, single-arm, phase 2a study (SAPHIRA1) - Davies, Jane C; Van de Steen, Olivier; van Koningsbruggen-Rietschel, Silke; Drevinek, Pavel; Derichs, Nico; McKone, Edward F; Kanters, Desirée; Allamassey, Lisa; Namour, Florence; de Kock, Herman; Conrath, Katja (Journal of cystic fibrosis, 2019)
BACKGROUND: Investigation of novel cystic fibrosis transmembrane conductance regulator (CFTR) potentiators, such as GLPG1837, for CF patients with gating mutations is challenging as trials require patients to withhold ivacaftor, the current standard of care. This study explored the feasibility of such a study and the impact of one-week ivacaftor withdrawal. METHODS: This open-label, single-arm study aimed to enrol 32 adults ≥18 years of age with CF and at least one p.Gly551Asp (G551D) mutation. Patients received three increasing GLPG1837 dosages twice-daily for two 7-day and one 14-day period following a one-week ivacaftor washout. The primary outcome was safety; secondary outcomes were changes in sweat chloride concentration, spirometry outcomes, and pharmacokinetics. RESULTS: Twenty-six patients enrolled; 24 completed the study. Adverse events were reported by 53.8-76.9% of patients (dosage-dependent), with respiratory adverse events most common. Mean sweat chloride concentrations decreased from 97.7 mmol/L (baseline) to 68.7 mmol/L (end of GLPG1837 treatment). In ivacaftor-pre-treated patients, mean sweat chloride concentrations rose from 42.5 mmol/L at screening to 98.5 mmol/L after ivacaftor washout. Levels were decreased following GLPG1837 treatment (to 68.8 mmol/L at treatment end). Percent predicted forced expiratory volume in 1 s declined from 73.3% at screening to 68.5% after ivacaftor washout but returned to screening level at treatment end (73.1%). CONCLUSIONS: Patient willingness to participate in the study suggests that the need for a short period of ivacaftor withdrawal may not be a barrier to development of novel potentiators, such as GLPG1837. A one-week ivacaftor washout was generally well tolerated, but resulted in a decline in lung function, which was reversed with GLPG1837 treatment to pre-washout levels. Combined with the concentration-dependent decrease in sweat chloride concentration, results show that GLPG1837 increases CFTR activity in G551D-CF patients. FUND: This work was supported by Galapagos NV. CLINICAL TRIAL REGISTRATION NUMBERS: NCT02707562; EudraCT 2015-003291-77.
Keywords: respirační funkční testy; výsledek terapie; Chloride Channel Agonists; aktivátory chloridových kanálů; protein CFTR; Drug Monitoring; Male; Sweat; Ivacaftor; pot; Cystic Fibrosis Transmembrane Conductance Regulator; chinolony; Aminophenols; pyrany; nenasazení léčby; Withholding Treatment; CFTR modulator; Cystic Fibrosis; vztah mezi dávkou a účinkem léčiva; Adult; Pyrazoles; Cystic fibrosis; aminofenoly; dospělí; mužské pohlaví; Quinolones; Treatment Outcome; Pyrans; náhrada léků; lidé; cystická fibróza; ženské pohlaví; GLPG1837; Humans; monitorování léčiv; G551D; Respiratory Function Tests; Gating mutation; Drug Substitution; Female; pyrazoly; Dose-Response Relationship, Drug